The other untold burden of cancer in sub-Saharan Africa: Anxiety and depressive symptoms among family caregivers of adult cancer patients - Joshua Kanaabi Muliira; Irene Betty Kizza (Elsevier, 2019)
Background: Cancer incidence in sub-Saharan Africa (SSA) is increasing and family caregivers (FCGs) play a critical role in ensuring good patient outcomes. FCGs face enormous caregiving and social demands, and this leads to psychological and mental health problems, for which they receive no support or care. Objective: To describe the extent of depression and anxiety symptoms among FCGs of adult cancer patients (ACPs) and the associated factors. Methods: A descriptive cross-sectional design and standardized scales (hospital anxiety and depression scale, caregiver reaction scale, and Katz index) were used to assess anxiety and depressive symptoms, and impact of caregiving on the physical health of 284 FCGs of ACPs in Uganda. Results: The majority of FCGs were caring for ACPs with stage 3 or 4 cancer (56%) and severe or very severe pain (73.1%). The prevalence of anxiety (35.2%) or severe anxiety (20%) and depression (48.2%) or severe depression (27.5%) symptoms were high. Anxiety was associated with self-rated health (OR [odds ratio] = 2.01; p = 0.013) and impact of caregiving on physical health (OR = 2.04; p = 0.000). Depression was associated with ACP pain (OR = 1.34; p = 0.030), ACP functional status (OR = 0.61; p = 0.004), time since cancer diagnosis (OR = 0.49; p = 0.010), FCG self-rated health (OR = 2.24; p = 0.007) and impact of caregiving on physical health (OR = 2.18; p = 0.000). Conclusions: The increasing incidence of cancer in SSA has led to high rates of poor mental health (anxiety and depression) among FCGs. Specific FCG and ACP factors can help us to identify FCGs at risk of depression and anxiety for early intervention. Keywords: Family caregiver, Cancer, Anxiety, Depression, Oncology, Uganda, Sub-Saharan Africa